Controlled degradation of polylactic acid grafting N‐vinyl pyrrolidone induced by gamma ray radiation. Issue 1 (30th April 2013) - Peng, Chaorong; Chen, Hao; Wang, Jingxia; Chen, Zhuping; Ni, Maojun; Chen, Yuheng; Zhang, Jing; Yuan, Tun
Abstract Polylactic acid (PLA) films were surface modified by gamma ray irradiation‐induced grafting of N‐vinyl pyrrolidone (NVP). The in vitro degradation behavior of polylactic acid grafting N‐vinyl pyrrolidone (PLA‐g‐PVP) copolymer was analyzed in terms of weight loss, molecular weight, and thermal properties. Grafting NVP significantly accelerated the degradation of PLA. The mass losses of the copolymers, which were less than that of pure PLA at the beginning of the degradation period, sharply accelerated with increasing degradation time. Moreover, the crystallization temperature decreased with increasing degradation time in the same graft ratio, and the degree of crystallinity increased. Cytotoxicity experiments and animal experiments in vivo were carried out to evaluate the biocompatibility of PLA‐g‐PVP copolymer. Varying graft ratios of PVP could control the degradation rate of copolymers, and thus broadening the applications of this material, such as in tissue engineering scaffolds, drug delivery, and prevention of postsurgical adhesion. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013